Dostosowanie prawa polskiego w zakresie niedozwolonych klauzul w umowach konsumenckich do regulacji unijnej - Rymanowska-Mrugała, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
Very often in a daily life consumers do not have any possibilities to negotiate the terms of contracts with entrepreneurs. They only have two options: either to agree with the proposed conditions and sign the contract or to reject it. This may cause situations in which such contracts might contain unfair clauses regarding the weaker party signing the contract. Polish accession to the European Union obliged Polish legislators to ensure maximum efficiency and to prevent comprehensive and coherent national law.The influence of implementation of Council Directive 93/13/EEC of April 1993 on unfair terms in consumer contracts to the Polish legal system is presented in the text. The main aim of the article is to compare Polish regulations on protecting consumers in the area of abusive clauses with the solutions adopted by the European Union. The author’s aim is also to indicate both positive and negative regulations in the Polish Civil Code regarding abusive contract terms in consumer’s contracts.
Keywords: klauzule abuzywne; ochrona konsumenta; dyrektywa 93/13